Pembrolizumab versus brentuximab vedotin in relapsed or refractory classical Hodgkin lymphoma (KEYNOTE-204): an interim analysis of a multicentre, randomised, open-label, phase 3 study. Issue 4 (April 2021) - Kuruvilla, John; Ramchandren, Radhakrishnan; Santoro, Armando; Paszkiewicz-Kozik, Ewa; Gasiorowski, Robin; Johnson, Nathalie A; Fogliatto, Laura Maria; Goncalves, Iara; de Oliveira, Jose S R; Buccheri, Valeria; Perini, Guilherme F; Goldschmidt, Neta; et al.
Summary: Background: PD-1 blockade via pembrolizumab monotherapy has shown antitumour activity and toxicity in patients with relapsed or refractory classical Hodgkin lymphoma. Here, we present interim analyses from the KEYNOTE-204 study evaluating pembrolizumab versus brentuximab vedotin for relapsed or refractory classical Hodgkin lymphoma. Methods: In this randomised, open-label, phase 3 study, patients aged 18 years or older with relapsed or refractory classical Hodgkin lymphoma with measurable disease and an Eastern Cooperative Oncology Group performance status of 0 or 1 who were ineligible for or had relapsed after autologous haematopoietic stem-cell transplantation (HSCT) were enrolled at 78 hospitals and cancer centres in 20 countries and territories. Patients were randomly assigned (1:1) with an interactive voice response system to pembrolizumab 200 mg intravenously every 3 weeks or brentuximab vedotin 1·8 mg/kg intravenously every 3 weeks. Randomisation was stratified by previous autologous HSCT and status after front-line therapy. Results from the second interim analysis are presented here, with a database cutoff of Jan 16, 2020. The dual primary endpoints assessed in the intention-to-treat population were progression-free survival as assessed by blinded independent central review, and overall survival (not analysed at this interim analysis). Safety was assessed in all patients who received at least one dose of the study drug. This study is registered with ClinicalTrials.gov, NCT02684292 . Recruitment for this trial is closed. Findings: Between July 8, 2016, and July 13, 2018, 151 patients were randomly assigned to pembrolizumab and 153 to brentuximab vedotin. After a median time from randomisation to data cutoff of 25·7 months (IQR 23·4–33·0), median progression-free survival was 13·2 months (95% CI 10·9–19·4) for pembrolizumab versus 8·3 months (5·7–8·8) for brentuximab vedotin (hazard ratio 0·65 [95% CI 0·48–0·88]; p=0·0027). The most common grade 3–5 treatment-related adverse events were pneumonitis (six [4%] of 148 patients in the pembrolizumab group vs one [1%] of 152 patients in the brentuximab vedotin group), neutropenia (three [2%] vs 11 [7%]), decreased neutrophil count (one [1%] vs seven [5%]), and peripheral neuropathy (one [1%] vs five [3%]). Serious treatment-related adverse events occurred in 24 (16%) of 148 patients receiving pembrolizumab and 16 (11%) of 152 patients receiving brentuximab vedotin. One treatment-related death due to pneumonia occurred in the pembrolizumab group. Interpretation: Pembrolizumab showed statistically significant and clinically meaningful improvement in progression-free survival compared with brentuximab vedotin, with safety consistent with previous reports. These data support pembrolizumab as the preferred treatment option for patients with relapsed or refractory classical Hodgkin lymphoma who have relapsed post-autologous HSCT or are ineligible for autologous HSCT. Funding: Merck Sharp & Dohme Corp (a subsidiary of Merck & Co, Inc, Kenilworth, NJ, USA). Translation: For the Portuguese translation of the abstract see Supplementary Materials section.